Systematic Literature Review of TCS34725 Sensor Applications in Various Fields - Anisa, Widya; Sari, Mona Berlian; Yohandri, Yohandri; Asrizal, Asrizal (Department of Physics, Universitas Negeri Padang, 2024)
The TCS34725 sensor, recognized for its precise color detection across the visible spectrum, is essential in agriculture, food safety, healthcare, security, and industry. As automation advances, reliable color detection systems are crucial for replacing subjective and inconsistent manual assessments. However, challenges such as varying lighting conditions and the need for advanced data processing techniques impact its accuracy and integration. Enhanced algorithms and machine learning applications enable real-time analysis, reducing human error and ensuring reliable results. The sensor's versatility supports applications such as monitoring crop ripeness, detecting harmful substances in food, and aiding medical diagnostics like urine analysis. This study conducts a systematic literature review to explore trends, advancements, and gaps in the sensor's applications. Findings emphasize its role in advancing Industry 4.0 by digitizing processes, fostering sustainable innovations, and improving operational efficiency, reliability, and quality of life.